2019
DOI: 10.1021/acs.biochem.9b00696
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Inhibits Aβ42 Aggregation and Prevents Aβ42-Induced Membrane Disruption

Abstract: Alzheimer’s disease (AD) is associated with self-assembly of amyloid β-protein (Aβ) into soluble oligomers. Of the two predominant Aβ alloforms, Aβ40 and Aβ42, the latter is particularly strongly linked to AD. Longitudinal studies revealed a correlation between AD and type 2 diabetes (T2D), characterized by abnormal insulin levels and insulin resistance. Although administration of intranasal insulin is explored as a therapy against AD, the extent to which insulin affects Aβ dynamics and activity is unclear. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…PICUP was applied to HP36 solution, following the published protocol used for Aβ and insulin. ,, In brief, stock solutions of each 1 mM tris­(2,2-bipyridyl)­dichlororuthenium­(II) hexahydrate (Sigma-Aldrich, St. Louis, MO) and 20 mM ammonium persulfate (APS) (Sigma-Aldrich) were prepared in a 10 mM sodium phosphate buffer. One μL of each stock solution was added to 18 μL of solubilized HP36 solution.…”
Section: Methodsmentioning
confidence: 99%
“…PICUP was applied to HP36 solution, following the published protocol used for Aβ and insulin. ,, In brief, stock solutions of each 1 mM tris­(2,2-bipyridyl)­dichlororuthenium­(II) hexahydrate (Sigma-Aldrich, St. Louis, MO) and 20 mM ammonium persulfate (APS) (Sigma-Aldrich) were prepared in a 10 mM sodium phosphate buffer. One μL of each stock solution was added to 18 μL of solubilized HP36 solution.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, it was shown that insulin decreases the quantity of Aβ peptides binding to the cell surface and hence inhibits Aβ aggregation . It was proposed that the inhibition of Aβ aggregation by insulin is due to the binding of insulin to Aβ peptides and Aβ aggregates. , Yet, the specific interactions of insulin with Aβ aggregates are still elusive. The long-term effect of intranasal insulin in AD patients showed that insulin is modifying AD-related pathophysiologic processes and not merely improving symptoms of memory impairment .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the interactions between insulin and Ab. Insulin can inhibit Ab aggregation, enhance Ab degradation, and prevent Ab-induced cellular events, such as membrane disruption and tau phosphorylation (Yamamoto et al, 2018;Long et al, 2019). On the other hand, Ab has also been found to modulate insulin signaling.…”
Section: Discussionmentioning
confidence: 99%